2012
DOI: 10.1002/hipo.22062
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal neurons inhibit meal onset

Abstract: There is extensive research regarding the neural mechanisms involved in satiety and meal termination; in contrast, there is very limited understanding of how meal onset is regulated. On the basis of several converging lines of evidence, we hypothesized that hippocampal neurons form a memory of a meal and inhibit meal onset during the postprandial period. As a first step, we tested whether reversible inactivation of the hippocampus with muscimol infusions after the end of one meal would accelerate the onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 86 publications
6
67
1
Order By: Relevance
“…Additionally, glucagon-like peptide-I (GLP-I) receptors in the ventral hippocampus also influence food intake and willingness to work to obtain food (i.e., "wanting"; [65,81]). Furthermore, there is solid evidence showing that hippocampal neurons form a memory of a meal and inhibit meal onset after a meal has been consumed [53,115,117]. These findings show that the hippocampus is a very likely target of the modulation exerted by interoceptive signal of hunger and satiety.…”
Section: Hippocampus and The Use Of Interoceptive Signals Of Hunger Amentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, glucagon-like peptide-I (GLP-I) receptors in the ventral hippocampus also influence food intake and willingness to work to obtain food (i.e., "wanting"; [65,81]). Furthermore, there is solid evidence showing that hippocampal neurons form a memory of a meal and inhibit meal onset after a meal has been consumed [53,115,117]. These findings show that the hippocampus is a very likely target of the modulation exerted by interoceptive signal of hunger and satiety.…”
Section: Hippocampus and The Use Of Interoceptive Signals Of Hunger Amentioning
confidence: 94%
“…In line with this notion, Huff, Emmons, Narayanan, & LaLumiere [68] have shown that the basolateral amygdala interacts with the ventral hippocampus to modulate specific types of learning (e.g., footshock learning) but not others (here context learning). This is also suggests that similarly, the hippocampus may not be one entity (e.g., [36,53,85,101]). For instance, while the ventral hippocampus has bi-directional connections to the amygdala, the dorsal hippocampus does not have any [33].…”
Section: Interactions Between the Amygdala And The Hippocampusmentioning
confidence: 99%
“…Parent and colleagues recently examined the impact of postprandial inactivation of hippocampal neurons on subsequent feeding behavior (21). After rats were trained to reliably and rapidly consume a 32% sucrose solution at a scheduled time daily, reversible inactivation of dorsal hippocampal neurons (via parenchymal GABA receptor agonist infusion) immediately following sucrose consumption decreased the latency to initiate feeding and increased the size of the subsequent chow meal.…”
Section: Hippocampal-dependent Mnemonic Influences On Feedingmentioning
confidence: 99%
“…For example, temporary inactivation of the dorsal hippocampus in rats decreases intermeal intervals [27], suggesting a diminished capacity for satiety signals to inhibit intake during the period following a meal. Furthermore, the conversion of circulating triglycerides to fatty acids increases following food intake, providing a source of satiety signals detectable in the brain [28].…”
Section: Supporting Datamentioning
confidence: 99%